Learning to adapt & adapting to learn - Using elements of outcome mapping in the ‘Resilient Adolescents in the Syria Crisis’ programme - van Ongevalle, Jan; Kvintradze, Ana; Rennesson, Gaël; Miller, David (Save the Children, 2021)
This learning paper highlights how elements of outcome mapping were used by Save the Children Sweden in a project (2018-2020) that supports adolescents, affected by the Syria crisis, to become more resilient. The paper first outlines how the spheres of influence framework has been applied to develop an actor focused theory of change. It then describes how progress markers, as an alternative to SMART indicators, were formulated to monitor the programme’s results. The paper also outlines how long lists of progress markers were categorised in a more realistic and practical results framework. The paper then continues to elaborate how outcome journals, qualitative data analysis techniques and regular review meetings and reflection workshops were utilised for data collection, for collective learning among programme stakeholders and for informing planning and programme adjustment. Various practical guidelines and tips on how to implement elements of outcome mapping are provided. The final part of the paper explores to what extent outcome mapping was able to foster several key enablers of adaptive programme management and highlights some of the challenges that programme stakeholders faced. Practical recommendations towards the use of outcome mapping in future programmes are also proposed.

Inspiring Radically Better Futures - Evidence and Hope for Impact at Scale in a Time of Crisis - Guijt, Irene; Mayne, Ruth (Oxfam, 2020)
The world faces converging crises of health, climate, gender and racial injustice and extreme economic inequality. The calls are mounting to ‘build back better’ to create more inclusive, caring and environmentally sustainable futures. But what evidence exists that this is possible? The Inspiring Better Futures case study series investigates whether radical change at scale is possible and how it was achieved. This paper synthesises 18 cases which show that people are already successfully building better futures, benefitting millions of people, even against the odds in some of the world’s toughest contexts in lower-income countries. Together they offer hope that transformative change and radically better futures after the pandemic are within reach.

Nuru Kenya transition from Nuru International, Kenya - Dillan, Haley; Ouma, Joel; Yamron, David (What Transformation Takes - Evidence of Responsible INGO Transitions to Locally Led Development Around the World, 2020)
This case study is an example of a phased transfer of ownership and responsibility from INGO Nuru International to Nuru Kenya, including the exit of all international staff. Post-transition, Nuru Kenya is managed entirely by Kenyan staff, although it continues to receive financial support from Nuru International. A lot of the elements described are aligned with Adaptive Management ways of working.

Monitoring, Evaluation and Learning in NGO Advocacy - Findings from Comparative Policy Advocacy MEL Review Project - Coe, Jim; Majot, Juliette (ODI and Oxfam, 2013)
For organizations committed to social change, advocacy often figures as a crucial strategic element. How to assess effectiveness in advocacy is, therefore, important. The usefulness of Monitoring, Evaluation and Learning (MEL) in advocacy are subject to much current debate. Advocacy staff, MEL professionals, senior managers, the funding community, and stakeholders of all kinds are searching for ways to improve practices – and thus their odds of success – in complex and contested advocacy environments. This study considers what a selection of leading advocacy organizations are doing in practice. We set out to identify existing practice and emergent trends in advocacy-related MEL practice, to explore current challenges and innovations. The study presents perceptions of how MEL contributes to advocacy effectiveness, and reviews the resources and structures dedicated to MEL.

Doing Accountability Differently: A 'Vertically Integrated' Approach - Amakom, Uzochukwu; Fashola, Temitope; Gay, Charles; Shutt, Cathy (Christian Aid, 2018)